High-Frequency Seafloor Acoustics - Jackson, Darrell. (The Underwater Acoustics Series, 2007)
High-Frequency Seafloor Acoustics is the first book in a new series sponsored by the Office of Naval Research on the latest research in underwater acoustics. This exciting new title provides ready access to experimental data, theory, and models relevant to high-frequency seafloor acoustics and will be of interest to sonar engineers and researchers working in underwater acoustics. The physical characteristics of the seafloor affecting acoustic propagation and scattering are covered, including physical and geoacoustic properties and surface roughness. Current theories for acoustic propagation in sediments are presented along with corresponding models for reflection, scattering, and seafloor penetration. The main text is backed up by an extensive bibliography and technical appendices.